Toward Ameliorating Insulin Resistance: Targeting a Novel PAK1 Signaling Pathway Required for Skeletal Muscle Mitochondrial Function - Rekha Balakrishnan; Pablo A. Garcia; Rajakrishnan Veluthakal; Janice M. Huss; Joseph M. Hoolachan; Debbie C. Thurmond (MDPI AG, 2023)
The p21-activated kinase 1 (PAK1) is required for insulin-stimulated glucose uptake in skeletal muscle cells. However, whether PAK1 regulates skeletal muscle mitochondrial function, which is a central determinant of insulin sensitivity, is unknown. Here, the effect of modulating PAK1 levels (knockdown via siRNA, overexpression via adenoviral transduction, and/or inhibition of activation via IPA3) on mitochondrial function was assessed in normal and/or insulin-resistant rat L6.GLUT4myc and human muscle (LHCN-M2) myotubes. Human type 2 diabetes (T2D) and non-diabetic (ND) skeletal muscle samples were also used for validation of the identified signaling elements. PAK1 depletion in myotubes decreased mitochondrial copy number, respiration, altered mitochondrial structure, downregulated PGC1α (a core regulator of mitochondrial biogenesis and oxidative metabolism) and PGC1α activators, p38 mitogen-activated protein kinase (p38MAPK) and activating transcription factor 2 (ATF2). PAK1 enrichment in insulin-resistant myotubes improved mitochondrial function and rescued PGC1α expression levels. Activated PAK1 was localized to the cytoplasm, and PAK1 enrichment concurrent with p38MAPK inhibition did not increase PGC1α levels. PAK1 inhibition and enrichment also modified nuclear phosphorylated-ATF2 levels. T2D human samples showed a deficit for PGC1α, and PAK1 depletion in LHCN-M2 cells led to reduced mitochondrial respiration. Overall, the results suggest that PAK1 regulates muscle mitochondrial function upstream of the p38MAPK/ATF2/PGC1α-axis pathway.